Beer Game as a gamification strategy applying Industry 4.0: more than an inventory game - Aguirre-Álvarez, Yenny Alejandra; Patino-Rodríguez, Carmen Elena; Maya-Iregui, Catalina María; Bolívar-Torres, Emmanuel (Universidad Pedagógica y Tecnológica de Colombia, 2024)
One of the great challenges in learning processes is to strengthen soft and technical skills in real context of the academic community with experiential strategies such as gamification, which is also aligned with the technological trends presented by Industry 4.0. This article proposes to document an adaptation of the Beer Game, as a gamification strategy using a scale factory model that simulates logistics processes with value addition. For this purpose, it describes and compares the traditional Beer Game and its version adapted to the Plant 4.0 SCM simulator to finally perform an analysis of principles, pillars and technologies of Industry 4.0 applied in the adaptation proposed here. The main result is the innovation in the articulation of the Beer Game as a gamification strategy and the application of Industry 4.0 as a value proposition to strengthen logistics concepts in profiles such as Industrial Engineer.